Digitalization in Open Economies Theory and Policy Implications - Vogelsang, Michael; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2010)
Digital strings are not visible, but affect all economic segments. This book studies the phenomenon of digitalization with the instruments of economics in order to explore the interdependencies between digitalization, economic policy, and macroeconomic variables of open economies. Digitalization is separated into the three components networks, IT services, and digital goods which are then incorporated into macroeconomic models of trade theory in open economies. This approach allows to formally describe the cross-effects between digitalization and macroeconomic variables of a country. Specifically, it is used to analyze interdependencies between macroeconomic variables and networks, IT services, and digital goods, and to determine the challenges of digitalization for economic policy and regulation.
Characteristics of the Digital Economy -- Digitalization -- Economic Theory -- Theoretical Foundations -- Networks in a Fragmentation Model -- IT Services in a General Equilibrium Macro-Model -- Model: Entry of a Digital Goods Producer -- Comparison of the Models -- Economic Policy -- General Political Perspectives -- Policy for Networks, Services, Digital Goods -- Integrating Theory and Policy -- Summary -- Appendices.
Keywords: Economics; International economics; Management information systems; Economics/Management Science; International Economics; Business Information Systems